2003
DOI: 10.1002/pd.600
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and clinical consequences of extremely high maternal serum PAPP‐A levels

Abstract: A multicentre study was carried out to determine the frequency and clinical consequences of extremely high maternal serum pregnancy-associated plasma protein (PAPP)-A. There was a total of 79 pregnancies with PAPP-A exceeding 5.0 multiples of the gestation-specific median in a series of 46 776 pregnancies tested (0.2%) at the 7 collaborating centres. Five pregnancies were lost to follow-up, one miscarried and one with Noonan's syndrome was terminated. Of the remaining 72 that ended in a live birth, one infant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…On the basis of previous studies, a cut‐off point below the fifth percentile was considered as abnormal for PAPP‐A MoM (low PAPP‐A) and fβ‐hCG MoM (low fβ‐hCG) (Smith et al , 2002; Cuckle et al , 2003; Dugoff et al , 2004; Krantz et al , 2004; Liu et al , 2004; Smith et al , 2004; Spencer et al , 2005; Smith et al , 2006).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of previous studies, a cut‐off point below the fifth percentile was considered as abnormal for PAPP‐A MoM (low PAPP‐A) and fβ‐hCG MoM (low fβ‐hCG) (Smith et al , 2002; Cuckle et al , 2003; Dugoff et al , 2004; Krantz et al , 2004; Liu et al , 2004; Smith et al , 2004; Spencer et al , 2005; Smith et al , 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Decreased first trimester PAPP-A concentrations are a predictor of adverse pregnancy outcome, with a significant reduction of the placental volume and its vascularization (38). Conversely, high levels of PAPP-A have generally no pregnancy consequences, except cases of placenta accretes (39). We showed that high levels of maternal serum PAPP-A concentrations at first trimester were significantly predictive of the presence of MMc at delivery in whole cord blood.…”
Section: Discussionmentioning
confidence: 60%
“…that microvascular dilatation is required as a compensatory mechanism to maintain sufficient circulation when larger artery constriction is present. Despite this, one previous study did not find any association between high first‐trimester PAPP‐A levels and adverse pregnancy outcome.…”
Section: Discussionmentioning
confidence: 67%